Race, Sex and Slavery: ‘Forced Labour’ in Central Asia and Afghanistan in the Early 19th Century - HOPKINS, B. D. (Modern Asian studies, 2008)
The word 'slavery' conjures images of cruelty, racial bigotry and economic exploitation associated with the plantation complex crucial to the Atlantic trading economy from the seventeenth to the nineteenth centuries. Yet this was only one manifestation of practices of human bondage. This article examines the practice of 'slavery' in a very different context, looking at Central Asia, Afghanistan and the Punjab in the early nineteenth century. Here, bondage was largely a social institution with economic ramifications, in contrast to its Atlantic counterpart. Slavery served a social, and often sexual function in many of these societies, with the majority of slaves being female domestic servants and concubines. Its victims were often religiously, rather than racially defined, although bondage was a cross-confessional phenomenon. The practice continued to be widespread throughout the region into the early twentieth century.